THU0417 READMISSION RISK AND QUALITY OF CARE IN PATIENTS PRESENTING TO THE EMERGENCY DEPARTMENT WITH GOUT FLARES. (13th June 2020) - Brunetti, L.; Vekaria, J.; Lipsky, P.; Schlesinger, N.
Abstract : Background: Gout is the most common form of inflammatory arthritis and its economic burden is substantial, with estimates for the overall cost exceeding 20 billion (US) annually. Contributing to the economic burden are hospital admissions and iatrogenic events associated with pharmacotherapy. Identification of modifiable risk factors would be an important contribution to clinical practice. Objectives: The aim of this study was to identify opportunities for enhancing gout care in patients presenting to the Emergency Department (ED) with gout flares. Methods: This retrospective cohort study used data from electronic medical records (EMR) at a large community hospital. All consecutive patients visiting the medical center ED with a primary diagnosis of gout from 1/1/2016 to 7/1/2019 were included. Patients were then followed for 90 days to determine whether they were readmitted to the ED for any reason. A chart review identified whether they were on appropriate medications in terms of gout flare management. All data were summarized using descriptive statistics. A multiple logistic regression was constructed to identify risk factors for ED utilization within 90 days of the index visit. Results: A total of 214 patients were included in the analysis. Most patients were male (79%), mean age was 59.4 ± 15.6 years, and mean Charlson comorbidity index was 0.5 ± 1.14. The most common medications prescribed during the ED visit included NSAIDs (41.6%), opioids (28%), corticosteroids (26.6%), and colchicine (21%). Allopurinol and febuxostat were initiated in the ED in 4.7% and 0.9%, respectively. Discharge medications for the management of gout included NSAIDs (37%), corticosteroids (34.6%), opioids (23.8%), colchicine (14%), febuxostat (7%), and allopurinol (6.5%). Of the patients sent home with an opioid, 40% were newly prescribed. An anti-inflammatory medication was not prescribed in 29.6% of patients discharged from the ED. Readmission within 90 days was recorded in 16.8% of patients. Of these readmissions, 33.3% were gout-related and 11.1% were cardiac related. After adjusting for age and comorbidity index, patients receiving colchicine were 2.8 times more likely (OR, 2.81; 95% CI, 1.12 to 7.02; p=0.027) to return to the ED within 90 days. The most common cause of readmission in this subset was gout-related (54.5%). Conclusion: Nearly 30% of patients were discharged from the ED without an anti-inflammatory medication, whereas initiation of urate lowering therapy was rare. Opiates were used frequently, but the indication was uncertain. Only 5.6% of subjects revisited the ED for gout-related diagnoses in the subsequent 3 months. Colchicine prescription was associated with an increased risk of gout-related ED utilization within 90 days. Treatment of gout in the ED is sub-optimal and often does not follow established guidelines. Disclosure of Interests: Luigi Brunetti Grant/research support from: Astellas Pharma, CSL Behring, Consultant of: Horizon Foundation of New Jersey, Janaki Vekaria: None declared, Peter Lipsky Consultant of: Horizon Therapeutics, Naomi Schlesinger Grant/research support from: Pfizer, AMGEN, Consultant of: Novartis, Horizon Pharma, Selecta Biosciences, Olatec, IFM Therapeutics, Mallinckrodt Pharmaceuticals, Speakers bureau: Takeda, Horizon